Pemberdayaan Perempuan Melalui Pelatihan Pembuatan Eskrim Berbahan Baku Lokal - Hendrawan, Hendrawan; Sulaeman, Lina; Naasyiah, Rifdah (Ma'soem University, 2025)
One of the main problems in Campakamulya Village is the large number of unemployed residents, while job opportunities in the village are relatively limited. The sector that can be developed to absorb productive labor in the village is the entrepreneurial sector. A Community Empowerment Program was implemented in Campakamulya Village to help overcome existing problems in the community. The purpose of this empowerment activity is to transfer knowledge and skills in food processing, especially ice cream making, to women in Campakamulya Village, to motivate the community to be independent in creating jobs, and as a means to combine modern elements in food processing with local wisdom. The method used with the Participatory Action Research (PAR) approach, which actively involves the community in activities to solve their problems. The results of this community service activity are that the participants of the empowerment program become proficient in making ice cream by utilizing raw materials available around the village and providing a distinctive taste of Puntang coffee using equipment available in each household, have new knowledge regarding the criteria for good raw materials in food processing, master the concept of sanitation and how to apply it in food processing (cooking activities) and daily life, and can make attractive food packaging for their own products.